Tinjauan Yuridis Problematika Pengaturan Short-Term Accomodation (Rumah Susun) di Indonesia - Juan, Davin (JURNAL MINUTA, 2024)
“Visi Indonesia Emas 2045” is a long-term development plan initiated by the Government of the Republic of Indonesia to escape the middle-income trap by leveraging the Indonesian demographic bonus. Considering the population decline experienced by South Korea and Japan, it is a relief for Indonesia to have this demographic bonus. On the other hand, it intensifies urban population density, potentially transforming “Visi Indonesia Emas 2045” into “Indonesia Cemas 2045” (Indonesian anxiety about their future itself). The increase in population numbers will tighten business competition, forcing individuals to demonstrate survival skills through innovative ideas, such as capitalizing on business opportunities like short-term accommodation triggered by the staycation phenomenon. Related business models threaten the conservative hotel industry sector. The absence of a legal framework addressing this issue in Indonesia has led to significant negative impacts due to legal vacuums surrounding the problem. The persistence of Asian values rejecting Western culture, such as consensual intimacy without holy matrimony, is evident, exacerbated by covert practices in the prostitution business exploiting legal loopholes associated with short-term accommodation. Unlike other countries such as Singapore, which have banned short-term accommodation practices, Indonesia has yet to establish a regulatory framework addressing this issue. This study employs a normative juridical approach to explore the problematic aspects arising from the Indonesian legal framework concerning short-term accommodation and compare it with the Singaporean regulatory framework on that issue.